Level of agreement between bite mark interpretation from intraoral scanner and wax sheets - Tjioe Felicia Gotami; Siti Salsabila Kirana; Rizki Tanjung; Muhammad Novo Perwira Lubis; Intan Farizka; Aryadi Subrata (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Bite mark analysis is an important part of medicolegal investigations, providing objective documentation and interpretation of patterned injuries that may represent human bite marks. Conventional analysis commonly uses wax sheets, while intraoral scanners represent a more modern approach. However, it remains unclear which method yields more reliable results, and few studies have compared the interpretations from these techniques. Purpose: To determine the level of matching bite mark interpretation produced through wax sheet and intraoral scanner. Method: A descriptive observational design was conducted using 57 maxillary study models that met the inclusion and exclusion criteria. Each model was impressed into a wax sheet to record the incisal pattern and scanned with an intraoral scanner to obtain a digital record. The two outcomes were then superimposed and scored according to correspondence: Score 0 = no match with the suspect’s tooth pattern; Score 1 = 1–2 matching incisal patterns; Score 2 = 3–4 matching incisal patterns; Score 3 = 5–6 matching incisal patterns. Results: The research results showed a score of 0 at 0%, a score of 1 at 3.5%, a score of 2 at 8.5%, and a score of 3 at 87.5%. Conclusion: This study obtained 0% with a score of 0, 3.5% with a score of 1, 8.5% with a score of 2, and 87.5% with a score of 3, indicating that the bite marks obtained from wax sheets and intraoral scanning demonstrated a high degree of similarity, and yielded comparable results